Sutureless Intrascleral Posterior Chamber Intraocular Lens Fixation: Analysis of Clinical Outcomes and Postoperative Complications - Liu, Jiannan; Fan, Wenxue; Lu, Xinyu; Peng, Shaomin (Journal of ophthalmology, 2021)
Purpose. To report a technique for performing sutureless intrascleral fixation of a posterior chamber intraocular lens (PC-IOL) and analyzing the clinical outcomes and postoperative complications. Study Design. 68 eyes of 66 patients who received the technique were studied retrospectively. Methods. The best-corrected visual acuity (BCVA), intraocular pressure (IOP), anterior chamber depth (ACD), IOL tilt and decentration, corneal topography (K1 and K2), and postoperative complications were determined at 3 months. Results. The mean preoperative BCVA was 1.63 ± 1.24 logMAR units, and the mean postoperative BCVA was 0.74 ± 0.59 logMAR units at 3 months (P<0.05). The mean preoperative IOP was 21.9 ± 12.6 mmHg, and the mean postoperative IOP was 16.9 ± 4.5 mmHg at 3 months (P = 0.001). The mean preoperative corneal topography (K1 and K2) was K1 = 42.14 ± 1.91 and K2 = 43.54 ± 1.51; the mean postoperative corneal topography (K1 and K2) was K1 = 43.03 ± 2.18 and K2 = 43.40 ± 1.71 at 3 months (P = 0.678 and 0.468, respectively). The mean preoperative spherical equivalent was +11.00 ± 13.19 diopters (D), and the mean postoperative spherical equivalent was +0.06 ± 0.86 D (P<0.005). The mean IOL tilt was 2.4 ± 1.7°, and the mean decentration was 0.35 ± 0.21 mm. The mean ACD was 4.31 ± 0.29 mm. Conclusions. The 27-gauge sutureless intrascleral PC-IOL implantation technique minimizes intraoperative injury, simplifies procedure, and provides good PC-IOL fixation with few postoperative complications.